Preparation of blue-colored Al@SiO2@(CuPc-SO3)2Ba pigments: Different silane coupling agents on the corrosion resistance properties and color performance. (February 2019) - Cao, Ming; Nie, Shuping; Lv, Yang; Wang, Zhicheng; Xia, Ru; Dong, Qiannian; Chen, Peng; Miao, Jibin; Qian, Jiasheng
Abstract: Blue-colored aluminum pigments with double layer structure Al@SiO2 @(CuPc-SO3 )2 Ba were prepared by a two-step process of surface modification. The aluminum pigments were firstly encapsulated using tetraethoxysilane (TEOS) and silane coupling agents as precursors. A kind of water-soluble organic dye CuPc-SO3 H was immobilized onto the surface of Al@SiO2 by liquid-phase deposition. SEM, FTIR, XRD and XPS were used to characterize the surface morphology and chemical structure of the Al@SiO2 @(CuPc-SO3 )2 Ba pigments. The effect of different silane coupling agents and optimum conditions on the two-step surface modification were studied. The corrosion results showed that the coupling agent with long alkyl chain could significantly improve corrosion resistance of aluminum pigments. Chromatism analysis indicated that the glossiness of Al@SiO2 @(CuPc-SO3 )2 Ba pigments decreased slightly and showed angle-dependent optical effect. Highlights: Blue-colored aluminum pigments with double layer structure Al@SiO2 @(CuPc-SO3 )2 Ba were prepared. The optimum conditions on the two-step surface modification were studied. The DBES modified aluminum pigments have better anticorrosion resistance than APTES and VTES ones. The Al@SiO2 @(CuPc-SO3 )2 Ba pigments showed angle-dependent optical effect.